Budidaya Cacing Lumbricus Rubellus dengan Media Limbah Jamur sebagai Bahan Dasar Kosmetik dan Obat-Obatan - Sari Yuniarti; Sunarjo Sunarjo; Laksni Sedyowati (University of Merdeka Malang, 2020)
Merjosari Village in Malang, which used to be still an agricultural area, has gradually narrowed due to the large number of housing developments by developers. This has an impact on reduced agricultural output, especially chili and tomatoes. Farmers and laborers are unemployed because of the decreasing number of their agricultural lands. The program aims to provide training on the use of mushroom waste in the form of grajen into worm breeding media, program implementation methods by providing outreach programs, training, and providing worm culture facilities and infrastructure for farmers. The results of the program show that farmers and laborers in Merjosari Village can carry out their own cultivation of the lumbricus rubellus worm by utilizing mushroom baglog waste (grajen). The results of the worm cultivation can be sold in the form of worms that can be used as animal feed, birds / poultry, fish, shrimp and so on, the basic ingredients of cosmetics and medicines, and worm feces (vermicompost) used for high-quality organic fertilizers, especially for plants such as flowers and fruit. For farmers and other communities, this program can create self-employment opportunities (entrepreneurship), improve the economy and family welfare, participate in maintaining the balance of ecosystems and the environment.DOI: https://doi.org/10.26905/abdimas.v5i2.4407